Análise das propriedades termoluminescentes e exoeletrônicas de dosímetros de CaSO4:Eu com adição de prata - Junot, Danilo Oliveira (2013)
The dosimetry of ionizing radiation is essential to procedures could be taken in order to maximize the beneficial effects that the use of such radiation can offer to society, as well as minimize damage from such radiation. As a result, different materials detectors have been proposed in the literature for use in personal and environmental dosimetry. Thermoluminescent detectors are widely used in these dosimetric procedures. The motivation of this work was to produce crystals of CaSO4 doped with unusual elements such as europium (Eu) and silver (Ag), including in the form of nanoparticles, prepared by an adaptation of the method developed by Yamashita (1971). The interest in the production of these materials was to investigate other methods of producing thermoluminescent materials. In the new growth route, the crystals were produced from calcium carbonate (CaCO3), by incorporating the dopants (Eu2O3 or Ag2O3) in a solution of sulfuric acid. Silver nanoparticles Ag(NP) were obtained through a synthesis route called polyol method, which is based on the reduction of Ag ions in a polyalcohol, in this case the ethylene glycol. The composites were obtained from the mixture of the base compound and glass or Teflon. The thermally stimulated exoeletronic emission of the new materials was investigated. Thermoluminescent characteristics as linearity, reproducibility, energy dependence, minimum detectable dose, fading and kinetics order were evaluated. The composites showed TL emission glow curves with a single peak centered around 200 ° C for samples containing Teflon and 230 ° C for samples with addition of glass. The new routes for the preparation of dosimeters were shown to be viable, being the dosimeter based on calcium sulfate doped with europium and silver nanoparticles (CaSO4:Eu,Ag(NP)), which provides the most intense TL emission between the preparations studied, being linear, reproducible, with low fading and low detection limit.